The Evaluation of Kindergarten Curriculum Content in DKI Jakarta (Third Year Research) - Dhieni, Nurbiana; Wulan, Sri (Indonesian Journal of Early Childhood Education Studies, 2016)
Based on the research results in the first and tsecond year on curriculum content evaluation in kindergarten that included the suitability of the curriculum being used with the children development stages, the curriculum orientation centered on the child, the suitability of the curriculum to the needs of children, the internalization of cultural values of Indonesian society into curriculum use, the ability to adapt curriculum development and information technology, and the simplicity of the curriculum to be implemented in learning. Still many kindergartens are not able to develop their own curriculum and even when some of them did develop a curriculum, it did not refer to the curriculum development scope of principles. Therefore, in the third year researchers have carried out as follows; developed the concept of curriculum drafting training for kindergarten in Jakarta; Validation of the theoretical concept of training on the preparationof kindergarten curriculum by early childhood specialists and curriculum; Revised concept based on the results of theoretical validation; Developing instruments to measure the effectiveness of the kindergarten curriculum training; Trial instrument measuring the effectiveness of kindergarten curriculum training preparation. The evaluation was conducted by assessing the kindergarten curriculum that has been developed by the kindergarten with a qualitative model. The curriculum assessment was carried out by curriculum specialists in Early Childhood Education (ECD).